Age‐related declines in ejaculate quality and sperm kinematics vary among strains of Japanese Quail (Coturnix japonica). Issue 1 (4th December 2019) - Farooq, Umar; Malecki, Irek A.; Mahmood, Misbah; Martin, Graeme B.
Abstract: For successful breeding programs, it is important to quantify the useful period of a male's reproductive life and it is often done simply by measurement of semen quality. This information is lacking for Japanese quail so we tested whether there is a decline in ejaculate quality and sperm kinematics with age, and whether the decline varies among strains. Nine males ( n = 9) from each of 5 strains (A, B, C, D and E) were subjected to 4 semen collections ( n = 16 per male) at 8, 16, 26 and 36 weeks of age. Ejaculate volume, sperm concentration and total sperm per ejaculate were measured, and sperm kinematics were analysed using a Sperm Class Analyser (SCA ® ). There was a significant effect of age for ejaculate volume, total sperm per ejaculate and per cent medium sperm. The effect of the interaction between age and strain was significant for percent progressive motile sperm, percent rapid sperm, velocity curvilinear, velocity straight line, velocity average path, linearity, straightness and beat cross frequency. Ejaculate volume peaked at Week 26 in all strains, while peak values for sperm concentration and total sperm per ejaculate were observed at Week 16 for most strains. There were declines in percent motile sperm, progressive motile sperm and rapid sperm, and in velocity curvilinear velocity, velocity straight line and velocity average path, by Week 16 for most strains. Linearity declined by Week 26 in some strains, and all strains showed a significant decline in beat cross frequency by that age. In conclusion, the ability of CASA to detect age‐related changes in sperm kinematics makes it a valuable tool for identifying the best males and thus improving quail flock fertility. It is essential that breeders understand that age affects both sperm production and sperm kinematics, and that the changes vary with strain.